Baclofen and naltrexone effects on alcohol self-administration: Comparison of treatment initiated during abstinence or ongoing alcohol access in baboons. (1st October 2017) - Holtyn, August F.; Kaminski, Barbara J.; Weerts, Elise M.
Highlights: Baclofen and naltrexone reduced alcohol intake when initiated during alcohol access. Baclofen and naltrexone failed to reduce alcohol intake when initiated during abstinence. Baclofen did not decrease alcohol seeking when initiated during alcohol access or abstinence. Naltrexone decreased alcohol seeking only when initiated during alcohol access. Lower doses were more effective when initiated during active drinking than abstinence. Abstract: Background: Baclofen, a GABAB receptor agonist, is under investigation as a pharmacotherapy for alcohol use disorder. Treatment with a pharmacotherapeutic can be initiated during alcohol abstinence or active drinking, which may influence treatment outcomes. This study examined whether baclofen treatment initiated and maintained during alcohol abstinence would reduce alcohol seeking and self-administration upon return to alcohol access, and whether effects differed from treatment initiated and maintained during ongoing alcohol access. Naltrexone was tested under similar conditions for comparison. Methods: Five baboons self-administered alcohol under a three-component chained schedule of reinforcement that modeled periods of anticipation (Component 1), seeking (Component 2), and consumption (Component 3). Alcohol was only available in Component 3. In Experiment 1, baclofen (0.1-1.8 mg/kg) or naltrexone (1.0-5.6 mg/kg) was administered daily beginning on the first day of a 5-day abstinence period and treatment was continued for 5 days of alcohol access. In Experiment 2, selected doses of both drugs were administered during ongoing alcohol access. Results: When treatment was initiated during alcohol abstinence, baclofen and naltrexone did not significantly reduce total alcohol intake (g/kg) or alcohol seeking. In comparison, when treatment was initiated during ongoing alcohol access, both baclofen (1.8 mg/kg) and naltrexone (3.2 and 5.6 mg/kg) significantly reduced total alcohol intake (g/kg). Naltrexone (5.6 mg/kg), but not baclofen, significantly reduced alcohol seeking. Conclusions: Initiation of baclofen treatment (or other alcohol use disorder treatments) during abstinence or active drinking may be an important factor in influencing efficacy and appropriate dose selection.